2000
DOI: 10.1016/s0002-9440(10)64788-8
|View full text |Cite
|
Sign up to set email alerts
|

Prominent Axonopathy and Disruption of Axonal Transport in Transgenic Mice Expressing Human Apolipoprotein E4 in Neurons of Brain and Spinal Cord

Abstract: The epsilon 4 allele of the human apolipoprotein E gene (ApoE4) constitutes an important genetic risk factor for Alzheimer's disease. Recent experimental evidence suggests that human ApoE is expressed in neurons, in addition to being synthesized in glial cells. Moreover, brain regions in which neurons express ApoE seem to be most vulnerable to neurofibrillary pathology. The hypothesis that the expression pattern of human ApoE might be important for the pathogenesis of Alzheimer's disease was tested by generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(86 citation statements)
references
References 69 publications
1
83
0
2
Order By: Relevance
“…Disrupted transport has been shown in AD (Cash et al, 2003;Praprotnik et al, 1996;Richard et al, 1989;Terry, 1996) and also amyotrophic lateral sclerosis (Williamson and Cleveland, 1999), however relatively few studies have examined this aspect of the disease (Kasa et al, 2000). Nonetheless, numerous factors implicated in AD including oxidative stress (de la Monte et al, 2000;Perry and Smith, 1997;Smith et al, 1995), APO e (Tesseur et al, 2000), and APP-L (Torroja et al, 1999) have all been shown to affect axonal transport. The observation that AbPP can serve as a kinesin cargo receptor (Kamal et al, 2000(Kamal et al, , 2001 as well as the inhibition of kinesin-dependent transport by tau overexpression (Ebneth et al, 1998;Stamer et al, 2002) should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Disrupted transport has been shown in AD (Cash et al, 2003;Praprotnik et al, 1996;Richard et al, 1989;Terry, 1996) and also amyotrophic lateral sclerosis (Williamson and Cleveland, 1999), however relatively few studies have examined this aspect of the disease (Kasa et al, 2000). Nonetheless, numerous factors implicated in AD including oxidative stress (de la Monte et al, 2000;Perry and Smith, 1997;Smith et al, 1995), APO e (Tesseur et al, 2000), and APP-L (Torroja et al, 1999) have all been shown to affect axonal transport. The observation that AbPP can serve as a kinesin cargo receptor (Kamal et al, 2000(Kamal et al, , 2001 as well as the inhibition of kinesin-dependent transport by tau overexpression (Ebneth et al, 1998;Stamer et al, 2002) should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Features of AD pathology in these animals include reduced numbers of presynaptic terminals in mice expressing apoE4 with (54,64) or without (53,66,68) expression of human amyloid precursor protein (APP), increased plaque deposition in apoE4 mice expressing APP (64), increased phosphorylation of tau (65)(66)(67), impaired learning and memory (55,69), and altered long-term potentiation (77).…”
Section: Apoe and Admentioning
confidence: 99%
“…Furthermore, the N-terminal domain of apoE3 is responsible for irreversibly binding to tau through the microtubule-binding repeat regions (56,152). Increased phosphorylation of tau has been observed in transgenic mice expressing human apoE4 in neurons but not in mice expressing apoE4 in astrocytes (65,66,129). Thus, apoE4 may have a neuron-specific effect on tau phosphorylation.…”
Section: Apoe4 Neuropathology Independent Of A␤ Apoe Cleavage In Neurmentioning
confidence: 99%
“…Such an outcome could explain why this organelle has a fragmented and atrophic morphology in neurons of patients with AD. 98 Interestingly, over expression of APOE ε4, as well as mutations in PS1 and APP, also affect tau phosphorylation, axonal transport, and neuronal dystrophy [99][100][101][102] in an Aβ-independent manner, which suggests a possible converging process underlying the familial and sporadic forms of the disease.…”
Section: Early Cytoskeletal Impairmentsmentioning
confidence: 99%